Evaluation of the effectiveness of the government programs in support of large families in the Republic of Kazakhstan - Tazhigalieva Г.К.; Askeeva Г.Б.; Gabdulina Б.А. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2023)
Family policy is important because families are the building blocks of society. Strong and healthy families contribute to the well-being of individuals, communities, and nations. A system of measures can help solve several social problems, such as poverty, inequality, and social exclusion. By supporting families, Governments can contribute to economic growth and social stability. The family policy has different approaches, depending on the political and cultural context. Some countries prioritize financial support for families, while others focus on providing services such as childcare and education. This policy may also be determined by demographic trends, such as population ageing and changing family structure. As a natural instrument of reproduction of the population, the family performs primarily the function of growth. In Kazakhstan, the government supports the pro-natalist format of family and demographic policy. A large family at the present stage of family and demographic policy acts as a supplier of human capital, as well as a carrier of certain risks, a trigger of some challenges in the development of society. Having many children is the cornerstone of related disciplines: political science, demography, economics, and psychology. There are various theories, models, and concepts of family policy, where researchers solve and propose various mechanisms for improving current measures of modern family policy.